KORELASI ANTARA PEMBELAJARAN INTENSIF BAHASA ARAB DENGAN PEROLEHAN NILAI TOAFL (TEST OF ARABIC AS A FOREIGN LANGUAGE) MAHASISWA UNIVERSITAS HASYIM ASY’ARI TEBUIRENG: KORELASI ANTARA PEMBELAJARAN INTENSIF BAHASA ARAB DENGAN PEROLEHAN NILAI TOAFL (TEST OF ARABIC AS A FOREIGN LANGUAGE) MAHASISWA UNIVERSITAS HASYIM ASY’ARI TEBUIRENG - Andreastya, Vian Hanes; Al Ta'dib, Fathur Rohman (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
Abstract: This article discusses the correlation between Arabic intensive learning with the score of TOAFL (Test of Arabic as a Foreign Language) Hasyim Asy'ari Tebuireng University students, aims to determine 1) the level of attendance of students in intensive Arabic learning, 2) the TOAFL score of students of Hasyim Asy'ari Tebuireng University, and 3) correlation between intensive Arabic learning and the TOAFL scores. With a quantitative approach with the type of ex-post facto, researchers use the Spearman correlation test. The results show that: 1) most classes (students) have good attendance rates (discipline), 2) most classes (students) also have TOAFL scores above the average value, and 3) there was no correlation between Learning Intensive Arabic Language with the TOAFL score gained of Hasyim Asyari University students is marked by the sig value obtained 0.614).